Non-motorized transport in developing countries : a case study in Dhaka, Bangladesh - Hossain, Md. Akhtar; Yordphol Tanaboriboon; Yasushide, Okuyama; Morisugi, Hisa; Nagarur, Nagendra N.; Government of Japan (Bangkok : Asian Institute of Technology, 1996)
Since independence of Bangladesh in 1971, Dhaka, its capital city had a boom both in population and physical size. As a result of this change, recurrent pressure on transportation has exhausted the available resources. Rickshaw, the non-motorized transport plays an important role in urban transportation system. This study focused on the rickshaw users and operators characteristics, and its impact to the other vehicles in Dhaka City. This study also developed the speed-density-flow relationships for rickshaw traffic. The rickshaw users and operators characteristics data were collected through questionnaire surveys. To collect speed data of motor vehicles both in VIP ( exclusive use for motor vehicles only ) and mixed modes routes, a license plate technique was employed. Speed, density, and flow data for rickshaw were collected by using photographic technique through a video camera. According to the questionnaire surveys, the rickshaw mode was 'not so safe but not so risky' while the speed is 'just right' as expressed by majority of the users. People wanted to use this mode because it was more convenient, providing door to door service, and shorter travel time. Because of over crowded, and poor level of services, the rickshaw users did not want to use public buses. Most of rickshaw drivers belong to the low income group with mostly have no education, and about 93% of the drivers did not have their own house. About 94% of the drivers were not the native of Dhaka city. A negative attitude was observed in regard to the policy on fixing the rental fee by the government. Generally, the rickshaw owners were within the low to intermediate income group with low education level. Some owners had other job i.e., rickshaw mechanics, small business ect. In all cases, a positive attitude was observed fo r the separation of this mode from other motorized vehicles by providing rickshaw lane or path in all routes to improve the traffic condition. It was observed that the speed of the motor vehicles in VIP and mixed routes during peak and off-peak periods were significantly different with 5% level of significance. The speed-density flow relationships for rickshaw traffic were calibrated by using six established models i.e., Greensheilds, Underwood, May's bell-shaped, Greenberg, 2-regime linear, and 3-regime linear model. It was observed that the non-linear models fit the data with high correlation coefficient r value than that of the linear models
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Civil Engineering
Thesis (M.Eng.) - Asian Institute of Technology, 1996
Keywords: Pedicabs